The scholarship of inter-faith engagement with others in the writings of contemporary muslim scholars - Shehu, Fatmir Mehdi (2009)
The acts of pride, arrogance, superiority, selfishness, enmity and disrespect for others, have created since the very beginning of human history a very hostile environment, which has been an immense obstacle for the construction of a friendly and mutual engagement among people. Such engagement can take place in different aspects of peoples’ daily activities, like religious, civilizational, political, sociological, cultural, economic, and so on. The most important engagement, which is related with peoples’ spiritual and material aspects of life, is, however, the inter-faith engagement. Although Allah (s.w.t.) has revealed to humanity only one Transcendental Way of Life called DÊn; yet people follow different ways by creating different religious communities living in a society characterized by diversity. Indeed, the scholarship of inter-faith engagement has been introduced in our contemporary time. However, guidelines for this scholarship have been addressed in the Qur’Én and applied by the Prophet (p.b.u.h.) fourteen centuries ago. This paper has attempted to discuss the scholarship of inter-faith engagement as promoted by the Qur’Én and its application in the lifetime of the Prophet (p.b.u.h.), as well as the approach of selected contemporary Muslim scholars towards this scholarship.